The immune landscape of myelodysplastic syndromes. (November 2016) - Fozza, Claudio; Crobu, Valeria; Isoni, Maria Antonia; Dore, Fausto
Abstract: Even though the pathogenesis of myelodysplastic syndromes (MDS) is dominated by specific molecular defects involving hematopoietic precursors, also immune mechanisms seem to play a fundamental functional role. In this review we will first describe the clinical and laboratory autoimmune manifestations often detectable in MDS patients. We will then focus on studies addressing the possible influence of different immune cell subpopulations on the disease onset and evolution. We will finally consider therapeutic approaches based on immunomodulation, ranging from immunosuppressants to vaccination and transplantation strategies.